2020
DOI: 10.1038/s41419-019-2199-4
|View full text |Cite
|
Sign up to set email alerts
|

ALG-2 couples T cell activation and apoptosis by regulating proteasome activity and influencing MCL1 stability

Abstract: T cell homeostasis is critical for the proper function of the immune system. Following the sharp expansion upon pathogen infection, most T cells die in order to keep balance in the immune system, a process which is controlled by death receptors during the early phase and Bcl-2 proteins in the later phase. It is still highly debated whether the apoptosis of T cells is determined from the beginning, upon activation, or determined later during the contraction. MCL1, a Bcl-2 family member, plays a pivotal role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The intracellular proteins observed were not due to a loss in cell viability (Supplemental Fig. S4B), consistent with a previous report and likely result of extracellular vesicles production (43).…”
Section: Mapping the T-cell Secretome Constituentssupporting
confidence: 91%
“…The intracellular proteins observed were not due to a loss in cell viability (Supplemental Fig. S4B), consistent with a previous report and likely result of extracellular vesicles production (43).…”
Section: Mapping the T-cell Secretome Constituentssupporting
confidence: 91%
“…To further explore the molecular mechanism of BSArGO@ZIF-8 NSs promoted Cal27 cell apoptosis, we use a series of varied methods to screen the apoptosis-related signaling pathways and genes. The bubble diagram based on KEGG enrichment analysis demonstrated that these DEGs were significantly enhanced in cell cycle, apoptosis pathway, and mitogen-activated protein kinase (MAPK) signaling pathways (Figure a), which have been confirmed to play key roles in regulating cancer cell growth and apoptosis. The heatmap showed that DEGs enriched in apoptosis signaling pathways were constituted of 11 up-regulated DEGs and 9 down-regulated DEGs, including for example Mcl1, FOS, JUN, CASP12, CASP2, BIRC3, and TNFRSF1A (Figure b). The Pathview analysis demonstrated that BSArGO@ZIF-8 NSs alter most genes in apoptosis-related signaling pathways, including down-regulation of α-tubulin, PARP, Lamin, TRAIL, TNF-R1, FADD, and CASP10, and up-regulating JNK, CytC, and Mcl-1 (Figure c). In addition, BSArGO@ZIF-8 NSs could change pro-apoptotic gene expression, up-regulating Fas-L, Bim, HRK, and down-regulating Fas.…”
Section: Resultsmentioning
confidence: 96%
“…ALG-2 was originally identified as a gene product required for apoptosis in mouse T-cell hybridomas [ 17 ]. Recently, He et al reported that ALG-2 interacts with Rpn3/PSMD3, a component of the 26S proteasome, resulting in promotion of the degradation of the BCL-2 family protein MCL1 in apoptotic T-cells [ 49 ]. That study highlights the potential pro-apoptotic function of ALG-2 in T-cells.…”
Section: Discussionmentioning
confidence: 99%